1997
DOI: 10.1021/bi9619177
|View full text |Cite
|
Sign up to set email alerts
|

Can a Two-State MWC Allosteric Model Explain Hemoglobin Kinetics?

Abstract: We have analyzed the nanosecond-millisecond kinetics of ligand binding and conformational changes in hemoglobin. The kinetics were determined from measurements of precise time-resolved optical spectra following nanosecond photodissociation of the heme-carbon monoxide complex. To fit the data, it was necessary to extend the two-state allosteric model of Monod, Wyman, and Changeux (MWC) to include geminate ligand rebinding and nonexponential tertiary relaxation within the R quaternary structure. Considerable sim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

15
116
0

Year Published

1997
1997
2017
2017

Publication Types

Select...
7
3

Relationship

2
8

Authors

Journals

citations
Cited by 107 publications
(131 citation statements)
references
References 67 publications
(135 reference statements)
15
116
0
Order By: Relevance
“…With time, r converts to t within R with a highly stretched exponential time course as observed in solution, and the rebinding rate to t in R asymptotically approaches the same rate as t in T. The fractional population of 20% for the t subunits, moreover, is very close to the 30-40% predicted from fitting the kinetics in solution with the TTS model under conditions that would be expected to favor more t (27). A result that strongly supports our interpretation of these experiments is that the stretching exponent of ∼0.2 is nearly identical to the exponent of ∼0.3 observed in solution for the unliganded heme spectral changes that were interpreted as corresponding to the r → t relaxation (27,42), but with a half-time that is ∼10 6 -fold larger due to slowing by the gel. The highly stretched exponential time course for the r → t tertiary conformational relaxation was previously explained by a theoretical model (43) that takes into account the dynamics of interconversion within the ensemble of conformational substates (21,44).…”
Section: Resultssupporting
confidence: 83%
“…With time, r converts to t within R with a highly stretched exponential time course as observed in solution, and the rebinding rate to t in R asymptotically approaches the same rate as t in T. The fractional population of 20% for the t subunits, moreover, is very close to the 30-40% predicted from fitting the kinetics in solution with the TTS model under conditions that would be expected to favor more t (27). A result that strongly supports our interpretation of these experiments is that the stretching exponent of ∼0.2 is nearly identical to the exponent of ∼0.3 observed in solution for the unliganded heme spectral changes that were interpreted as corresponding to the r → t relaxation (27,42), but with a half-time that is ∼10 6 -fold larger due to slowing by the gel. The highly stretched exponential time course for the r → t tertiary conformational relaxation was previously explained by a theoretical model (43) that takes into account the dynamics of interconversion within the ensemble of conformational substates (21,44).…”
Section: Resultssupporting
confidence: 83%
“…3. Measurements made by linearly polarized absorption spectroscopy of T state crystals showed that the Hill coefcient of 1.0 in the crystals resulted from the ®¯inequiv-alence (which would produce anti-cooperativity) being compensated by an approximately equal amount of positive cooperativity within the ®¯dimer in the T state (37 ). These departures from a pure MWC model are small; the ®¯inequivalence being 5 or less, and the dimer inequivalence being »2% at the quaternary-linked binding strengths and cooperativity.…”
Section: Appendixmentioning
confidence: 97%
“…This approach has been very useful when starting with ligand-saturated hemeproteins. Nanosecond and faster photodissociation of ligand-bound hemoglobins has shed considerable light on the sequence of molecular steps associated with the tertiary and quaternary structure changes in the globin that follow ligand dissociation (2)(3)(4)(5)(6)(7)(8)(9)(10).…”
mentioning
confidence: 99%